Effect of spectinomycin on T. pallidum in incubating experimental syphilis. Issue 5 (October 1975) - Petzoldt, D
Abstract : Animal experiments were performed to determine if a single-dose treatment for acute gonorrhoea with 2 g. spectinomycin could cure a simultaneously acquired syphilis at a very early stage of incubation. 300 treponemes (Nichols stain T. pallidum) were inoculated intratesticularly and 3 days later spectinomycin was administered in a dose which produced spectinomycin serum levels similar to those in patients who had received a single oral dose of 2 g. This dosage of spectinomycin did not prevent the development of syphilitic orchitis or reactivity to the FTA-ABS test, but it prolonged the subclinical incubation period.